2020
DOI: 10.3390/v12101126
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Viral RNA Genomes and the RNA Folding Problem

Abstract: Viral RNA genomes change shape as virus particles disassemble, form replication complexes, attach to ribosomes for translation, evade host defense mechanisms, and assemble new virus particles. These structurally dynamic RNA shapeshifters present a challenging RNA folding problem, because the RNA sequence adopts multiple structures and may sometimes contain regions of partial disorder. Recent advances in high resolution asymmetric cryoelectron microscopy and chemical probing provide new ways to probe the degree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…The E RMSD (with a cutoff of 100), which enforces the secondary structure, increases by around 5% in both cases, which expresses that the structure of the restrained stems is minimally affected. An optimal determination of the 3D encapsidated structure of the RNA genome goes beyond the capabilities of the current RNA-protein interaction modeling, which was discussed and conceptualized under different hypotheses, specifically for virus assemblies [44][45][46][47]. Nevertheless, we aim to present a systematic and reasonable model, which brings a new methodology, to structurally interpret, explain and evaluate the feasibility of the chemically probed secondary structures and the further microscopic characteristics of confined RNA inside virus capsids.…”
Section: Resultsmentioning
confidence: 99%
“…The E RMSD (with a cutoff of 100), which enforces the secondary structure, increases by around 5% in both cases, which expresses that the structure of the restrained stems is minimally affected. An optimal determination of the 3D encapsidated structure of the RNA genome goes beyond the capabilities of the current RNA-protein interaction modeling, which was discussed and conceptualized under different hypotheses, specifically for virus assemblies [44][45][46][47]. Nevertheless, we aim to present a systematic and reasonable model, which brings a new methodology, to structurally interpret, explain and evaluate the feasibility of the chemically probed secondary structures and the further microscopic characteristics of confined RNA inside virus capsids.…”
Section: Resultsmentioning
confidence: 99%
“…Apart from this, the genome remains largely disordered. This contrasts with the MS2 genome, where 80% of nucleotides can be individually resolved (multiple conformers still exist, however) [67], implying a much higher degree of structural order to the RNA within the virion in the latter.…”
Section: Other Techniquesmentioning
confidence: 86%
“…A field of study that high-resolution cryo-EM is particularly useful for is imaging the RNA packaging structure within the nucleocapsid of viruses. Asymmetric reconstructions of Brome mosaic virus (BMV) and MS2 bacteriophage have been completed and revealed differing levels of RNA packaging [67]. Analysis of BMV at 3.9 angstrom resolution showed that the capsid protein interacts with the gRNA at the two-and threefold vertices, with the RNA forming different conformations.…”
Section: Other Techniquesmentioning
confidence: 99%
“…The lack of a solid understanding of the connection between self-assembled structures of biopolymers such as RNA, 37,38 induced by specific internucleotide interactions, and their modification as a result of the adsorption process, induced by less specific interactions with the adsorbing substrate, is a challenge whose general aspects we aim to address in this work.…”
Section: Introductionmentioning
confidence: 99%